PENGARUH PENAMBAHAN SUMBER KARBON TERHADAP KONDISI FISIK NATA DE COCO - Hamad, Alwani; Andriyani, Nur Afifah; Sutopo, Heru; Wibisono, Haryo (Techno Jurnal Ilmu Teknik, 2011)
Nata de coco is one of the functional food made from coconut milk which is processed through fermentation by using acetic acid bacteria, Acetobacter xylinum. It convert glucose into cellulose in coconut wate medium. Undigested cellulose consumed in the body that it will benefit to the human digestive system. The formation of nata requires a source of C, H, N, and minerals. Coconut water have already contains most of the nutrients it needs, but still needs to be enriched with other nutrient sources added. As a source of sugar can be added sucrose, glucose, fructose, starchs and flour maezena. This study aims to determine the physical properties of nata with different carbon sources. The addition of fructose would produce nata de coco with the most optimum yield at 0.755 g nata / ml coconut water with 8.41 mm thickness, 3.92 g wet weight and dry weight of 0.47 grams. However, nata produced has a less chewy texture with 87.56% moisture content. Key-word: Nata de coco, source of carbon, coconut water, Acetobacter xylinum